Numerical Investigation of Soft Ground Improvement beneath Road Embankments Using Prefabricated Vertical Drains: Insights from PLAXIS 2D Modeling - Muh Miftahulkhair; Irma Ridhayani; Nur Okviyani; Herni Suryani; Ellyyni Dwi Fortuna (Universitas Sulawesi Barat, 2025)
Abstract Soft clay deposits often cause excessive settlement and instability in road embankments. This study investigates ground improvement using prefabricated vertical drains under staged embankment loading through finite element modeling in PLAXIS 2D. The analysis examines consolidation rate, settlement, pore water pressure dissipation, and safety performance for square and triangular drain layouts with spacings of 1.25 m and 1.50 m. Results show that vertical drains accelerate consolidation, reducing the time to reach 90 percent settlement from 8.3 years to less than 3 years, while improving overall embankment stability. The triangular 1.25 m configuration produced the most uniform deformation and fastest consolidation response. The study confirms that optimized drain geometry significantly enhances soft ground performance and provides a practical numerical framework for design applications in tropical regions.